2020
DOI: 10.3389/fcell.2020.00374
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulates Fungal Virulence and Sexual Reproduction in Cryptococcus neoformans

Abstract: Autophagy (macroautophagy) is an evolutionarily conserved degradation pathway involved in bulk degradation of cytoplasmic organelles, old protein, and other macromolecules and nutrient recycling during starvation. Extensive studies on functions of autophagy-related genes have revealed that autophagy plays a role in cell differentiation and pathogenesis of pathogenic fungi. In this study, we identified and characterized 14 core autophagy machinery genes (ATGs) in C. neoformans. To understand the function of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Our data suggest that Flc1 regulates vacuolar fusion under stress conditions. Autophagy is a catabolic process induced by diminishment of nutrient availability that requires vacuolar fusion mediated by the TOR pathway ( 39 ). We hypothesized that C. neoformans Flc1 plays a role in the starvation response by regulating TOR-mediated vacuolar fusion and autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggest that Flc1 regulates vacuolar fusion under stress conditions. Autophagy is a catabolic process induced by diminishment of nutrient availability that requires vacuolar fusion mediated by the TOR pathway ( 39 ). We hypothesized that C. neoformans Flc1 plays a role in the starvation response by regulating TOR-mediated vacuolar fusion and autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that it is crucial to C. neoformans infection (Figure 1). A recent study surveyed an in vivo virulent phenotype seen in 14 C. neoformans autophagy gene knockout strains, and the results showed that autophagy is essential for fungal survival in the host 33 . These mutants also showed impaired basidiospore production and the inability to undergo meiosis 33 .…”
Section: Autophagy-related Genes and Fungal Pathogenicitymentioning
confidence: 99%
“…A recent study surveyed an in vivo virulent phenotype seen in 14 C. neoformans autophagy gene knockout strains, and the results showed that autophagy is essential for fungal survival in the host 33 . These mutants also showed impaired basidiospore production and the inability to undergo meiosis 33 . The VPS34 gene in C. neoformans is involved in the autophagy of ascomycete yeast, regulating the formation of autophagy-related 8-labeled (ATG8-labeled) vesicles 34 .…”
Section: Autophagy-related Genes and Fungal Pathogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy also plays major roles during sexual development in fungi [ 179 , 188 , 189 , 190 , 191 , 192 ]. During sexual reproduction, a developmental specific removal of peroxisomes takes place during ascospore development in P. anserina .…”
Section: Fungal Development Also Relies On the Autophagic Removal mentioning
confidence: 99%